A comparison of soil organic carbon and total nitrogen stock capacity in adjacent cultivated, agriculture and forest soils - Savaci, Gamze; Sariyildiz, Temel (Bursa Technical University, 2018)
Land use type and change cause perturbation of the ecosystem and can influence the Carbon (C) stocks and fluxes. In particularly, conversion of forest to agricultural ecosystems affects several soil properties but especially soil organic carbon (SOC) concentration and stock. In this present study, main aim was to assess the differences in soil organic carbon and total nitrogen contents and stock capacities in adjacent cultivated land (wheat production-CS), agriculture (walnut garden- WS and apple garden-AS), forestland (black pine-BS) and mixture of cultivated + poplar (CS+PS) lands. Soil samples were collected from six soil depths (0-5 cm, 5-10 cm, 10-15 cm, 15-20 cm, 20-25 cm, 25-30 cm) and analyzed for soil pH, soil texture, bulk density, soil organic carbon (SOC) and total nitrogen (TN) contents and stock capacities. Results showed that the BS had the highest mean SOC (9.52%), followed by the WS (4.84%), the CS + PS (4.83%), the CS (4.43%) and AS (3.85%). Mean TN content was also highest in the BS (0.63%) followed by the CS (0.157%), the AS (0.154%), the CS + PS (0.147%) and the WS (0.131%). Mean SOC stock capacity was highest for the BS (246 mg C ha-1), followed by the WS (146 mg C ha-1), the CS + PS (141 mg C ha-1), the CS (132 mg C ha-1) and the AS (111 mg C ha-1). Mean total N stock capacity was 4.70 mg N ha-1 for the CS, 4.37 mg N ha-1 for the AS, 4.28 mg N ha-1 for the CS + PS, 4.14 mg N ha-1 for the BS and 3.93 mg N ha-1 for the WS. In conclusion, the results indicate that land use type can significantly influence the soil organic carbon and total nitrogen dynamics in the northeast part of Turkey.
Keywords: Mühendislik; agriculture soil; forest soil; Engineering (General). Civil engineering (General); Forest soil; Agriculture soil; Soil organic carbon; Total nitrogen; Stock capacity; soil organic carbon; Engineering; total nitrogen; stock capacity; TA1-2040; 2. Zero hunger; 15. Life on land